Settlement of axially loaded pile groups in inhomogeneous soil. Issue 3 (2nd September 2018) - Crispin, Jamie J.; Leahy, Colm P.
Abstract : Accurate prediction of settlement is key to performance-based design of pile groups. Simple methods based on physically motivated modelling assumptions, in conjunction with wisely chosen soil material constants, can accurately predict settlements without having to perform complex numerical analysis in three dimensions. Interaction factors, introduced by Poulos, simplify the analysis of pile groups through superposition of the effects of only two piles at a time. Closed-form solutions for interaction factors between piles in homogeneous soils are available in the literature, incorporating both the displacement field around a single pile and the reinforcing effect of a second pile. This paper will investigate pile groups embedded in inhomogeneous soils with shear modulus varying with a power law function of depth. The problem is formulated by considering the response of a 'receiver' pile carrying no load at its head, subjected to the displacement field of a loaded 'source' pile. A simplified approximate expression is developed using a model error correction factor that is suitable for routine design use. The performance of the proposed model at predicting experimental results is investigated. Dimensionless design charts and an illustrative example are provided.